Phytoplankton mean cell size and total biomass increase with nutrients are driven by both species composition and evolution of plasticity - Matthiessen, Birte; Hattich, Giannina S. I.; Pulina, Silvia; Hansen, Thomas; Reusch, Thorsten B. H.; Hamer, Jorin (WILEY, 2025)
Community trait variability can arise from the species, genotypic, or individual plastic level. Trait changes on these levels can occur simultaneously, interact, and potentially translate to community functioning. Thus, they are crucial to realistically predict community functional changes. Using a phytoplankton model community comprising a diatom and a coccolithophore each with nine genotypes varying in cell size, we conducted a selection experiment over 130 generations towards nutrient availability. According to our expectations, mean community cell size and total biomass increased with increasing nutrient availability. Interspecifically, these community level changes were driven by shifts in species composition towards the larger diatom. Changes caused by intraspecific shifts did not result from sorting according to genotypes' standing variation in cell size in the first place. Instead, intraspecific changes likely resulted from the selection for a highly plastic diatom genotype, which led to a phenotypic distribution with larger cells in high and smaller cells in lower nutrient concentrations. We suggest that besides interspecific species sorting, the evolution of size plasticity through genotype selection represented an intraspecific contribution to mean community size increase with increasing nutrient availability that ultimately translated to increased total biomass. Our results demonstrate that all three levels on which trait changes can occur, regulate phytoplankton community-level functional changes and thus should be considered when predicting community change on ecological time scales.